PERILAKU KONSUMTIF TERHADAP PAKAIAN PERSPEKTIF HUKUM ISLAM: Studi Kasus Mahasiswi STAI YAPIS Takalar - Nurfitrihariani (Dahzain Nur, 2022)
Clothing is a basic need in life. In addition to protecting us from exposure to the sun, clothes are also a representation of the wearer. In this growing era, the development of fashion, especially clothing fashion, also develops so as to form a new culture called consumerism culture. This culture arises as a result of people's behavior patterns that are increasingly consumptive towards something, especially clothing. This behavior arises due to a lack of self-control over an item. Buying an item is sometimes based on a desire not a need factor. Consumptive behavior causes various impacts, one of which tends to be wasteful. Often buying goods causes old items to pile up in the wardrobe. In Islam, it is taught that every human behavior has been regulated, even about how to spend our money or property. Later in the hereafter all our property will be accounted for or held accountable. The reality that happened to the stay YAPIS takalar student, there were many of them who shopped so often that the things in their closet piled up.